The need of international Islamic standards for medical tourism providers: a Malaysian experience - Kamassi, Ahmed; Abdul Manaf, Noor Hazilah; Omar, Azura (Emerald Group Publishing Ltd., 2020)
Purpose: The purpose of this study is to confirm that there is a great need for international Islamic accreditation body as a response of the growing number of the Islamic-friendly hospitals and Islamic practices among medical tourism providers across the globe, with a specific focus on the Malaysian industry. Design/methodology/approach: This paper systematically reviews the content of medical tourism studies and international accreditation organizations for health-care providers from literature to meet its objective. Findings: The establishment of international Islamic accreditation body becomes necessary nowadays as the response of the growing of Islamic medical tourism market. Creating standards based on Islamic laws and ethics may assess medical tourism providers when dealing with Muslim medical tourists. Furthermore, the most important benefit of Islamic accreditation is the development of uniform standards for Islamic medical tourism practices that combines health care and tourism services together. Practical implications: An international Islamic accreditation body should be developed to assist practitioners and policymakers to use standards to select policies to improve Islamic medical tourism practices, which in turn may facilitate the identification of effective services that can meet Muslim medical tourists’ needs and expectations. Originality/value: This study is the first that suggests the need to establish an international Islamic accreditation organization that assesses hospitals to offer Islamic medical tourism practices for Muslim medical tourists. It may contribute and add value to the body of Islamic medical tourism.